Floor finish selection in health-care facilities: a systematic literature review. Issue 13 (7th October 2019) - Dixit, Manish K.; Singh, Shashank; Lavy, Sarel; Yan, Wei
Abstract : Purpose: The purpose of this paper is to identify, analyze and discuss floor finishes used in health-care facilities and their selection criteria in the form of advantages and disadvantages. The authors also identify the top three health-care floor finishes and selection criteria based on the literature review results. Although flooring materials have a considerable impact on the life-cycle cost and indoor environment of health-care facilities, what criteria may be used for such flooring choices is not thoroughly studied. Design/methodology/approach: The authors performed a systematic review of the literature on certain flooring systems currently used in health-care facilities and the criteria applied for their selection. Peer-reviewed studies and articles published after Year 2000 consistent with the research design were included. Findings: Sixteen different selection criteria that influence the choice of floor finishes in health-care facilities were determined and discussed. The results show that the top three-floor finish materials preferred in health-care facilities are sheet vinyl, rubber and carpet, and the top three selection criteria for floor finishes are indoor air quality, patient safety and infection control. Originality/value: The results of this study will assist building owners, architects and interior designers with implementing an informed design decision-making process, particularly in relation to floor finish selection. The findings will also provide guidance to floor finish manufacturers to improve their products based on facility managers' preferences.